Increasing of Plasma Cholecystokinin Level and Jejunum Histological Changes After Treatment with Soybean Extracts Protein - MEILINAH HIDAYAT; JEANNY ERVIE LADI (HAYATI Journal of Biosciences, 2012)
It is well known that soybean has beneficial health effects. There are lot of active compounds in soybean, like protein and anti nutrition factors (ANF). Trypsin inhibitor and lectin, two kinds of ANF have an adverse effect on the morphology and function of digestive tract in animals. b-conglycinin in soybean protein, has been proven  has reducing body weight effect through increasing cholecystokinin (CCK) level. The aim of this study was to measure plasma CCK level and the histological changes of jejunum in Wistar rats after treatment with protein extract of Willis raw soybean (PEWS), protein extract of Detam 1 raw soybean (PEDS) and protein extract of Detam 1 tempeh (PEDT) for 14 days. This study was also to ascertain whether b-conglycinin and ANF contribute  to  reducing body weight by giving PEWS, PEDS, and PEDT to 4 groups of 6 rats for 14 days. We observed food intake, body weight, CCK level, and histological profile of jejunum. As a conclusion, PEWS, PEDS, and PEDT treatment to Wistar Rats  for 14 days caused increasing CCK plasma level and jejunum villi atrophy. The reducing body weight is caused not only by b-conglycinin but probably by ANF as well.